Mostefa El-ACHERAF: His position about Islam and his conception of socialism in the project of the Algerian liberation revolution from the book "Algeria: aNation and aSociety" - rehaili, hayet (The Algerian Historical Journal, 2026)
This study aims to address an important topic within the topics of the contemporary history of Algeria, which is the perception of the state and society project in the thought of the Algerian intellectual elite, specifically Mustafa Al-Achref as a model for a generation of Algerian thinkers who lived during the revolutionary period and the post-independence period, and we have chosen to track his position on Islam and socialism through his book The famous "Algeria, nation and society" Whoever studies this book deeply can clearly see the dominance of the cultural, ideological, linguistic and national problem over the content, and this is due to the author’s desire to follow the method of modernization and openness to the areas of identity and culture, which can only be achieved through a serious study of the realities of society before adopting any ideology.